A Checklist of the Seaweeds of the Mediterranean and Atlantic Coasts of Morocco. IV. Rhodophyceae - Ceramiales - Benhissoune, S.; Boudouresque, C.-F.; Perret-Boudouresque, M.; Verlaque, M. (Botanica marina, 2003)
A checklist of Moroccan Ceramiales (Rhodophyceae), based on both literature records and some original data, is presented. The distribution of each taxon for this region (12 Mediterranean and 26 Atlantic localities) is given. Using present-day taxonomy, 161 species and infraspecific taxa of this order are accepted for the Moroccan coasts.